The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/bfb0054891
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up Pollard's rho method for computing discrete logarithms

Abstract: In Pollard's rho method, an iterating function f is used to define a sequence (yi) by yi+l = f(yi) for i = 0, 1, 2,..., with some starting value yo. In this paper, we define and discuss new iterating functions for computing discrete logarithms with the rho method. We compare their performances in experiments with elliptic curve groups. Our experiments show that one of our newly defined functions is expected to reduce the number of steps by a factor of approximately 0.8, in comparison with Pollard's originally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 15 publications
1
82
0
2
Order By: Relevance
“…This implies these collisions not only have always occurred but the probability of a collision has also significantly increased if it compared with original method. It can be concluded that the proposed improved method will be better than the original pollard's Rho method and these alternative collisions can also be applied to previo us proposed improvements such that dividing the group into about 20 sets (Teske, 1998;2001). …”
Section: Comparison Between Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…This implies these collisions not only have always occurred but the probability of a collision has also significantly increased if it compared with original method. It can be concluded that the proposed improved method will be better than the original pollard's Rho method and these alternative collisions can also be applied to previo us proposed improvements such that dividing the group into about 20 sets (Teske, 1998;2001). …”
Section: Comparison Between Methodsmentioning
confidence: 97%
“…Despite the fact that there are several attacking methods to resolve ECDLP, Pollard's Rho method (Pollard, 1980) not only is at present known as the fastest algorithm to resolve the discrete logarithm problem on elliptic curves, but its parallelized variant as well because its mathematical operations is less than other methods like Baby-Step Giant-Step (Shanks, 1971). This encourages researchers to utilise from automorphism of the group (Duursma et al, 1990), random walk on certain equivalence classes (Wiener and Zuccherato, 1999;Gallant et al, 2000), parallelization (Oorschot and Wiener, 1999), iteration function (Teske, 1998;2001), negation map (Wang and Zhang, 2012) or cycle detection (Brent, 1980;Cheon et al, 2012;Ezzouak et al, 2014) to improve this attacking method. This paper will provide a new approach by using the theorem that proposed by (Sadkhan and Neamah, 2011) to improve Pollard's Rho method which use alternative collisions to resolve the ECDLP.…”
Section: Introductionmentioning
confidence: 99%
“…Montenegro, Kim, and Tetali [9] showed that for Pollard's Rho walk τ = O(log 3 N ), while Hildebrand [8,18] showed that for Teske's additive walk τ = O * (N 2/(r−1) ). A slightly weaker notion of mixing should be used for Teske's process when r < 6, but we do not consider it here.…”
Section: Pollard's Rho Methodsmentioning
confidence: 99%
“…However, each processor could be working to find a different discrete logarithm as long as the iterating function used by all processors does not depend on the group element whose logarithm is sought. This requirement is satisfied by an iterating function f : G → G suggested by Teske [18], where G is partitioned into about 20 disjoint sets T i , each set is assigned a fixed randomly chosen group element g xi with known logarithm x i , and f (y) = yg xi if y ∈ T i .…”
Section: Pollard's Rho Methodsmentioning
confidence: 99%